2015
DOI: 10.1136/ejhpharm-2015-000723
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the information about procedures after cold chain disruption provided by pharmaceutical industry to hospital and community pharmacies

Abstract: PurposeTo compare the response of the pharmaceutical industry to information requests from a hospital pharmacy and a community pharmacy regarding the inadvertent exposure of refrigerated medicines (2–8°C) to out-of-range temperatures.MethodsA complete list of all authorised medicines labelled for refrigeration was obtained from the Portuguese Medicines Agency. A standard information request regarding cold chain disruption for refrigerated medicines was sent to pharmaceutical companies from a hospital and a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…e world public medicine field is concerned with the reality of information transparency. e existing research focuses on the transparent supervision of drug information, transparency of the pharmaceutical industry chain in all aspects, and subject of participation [24][25][26]. For example, Vian et al [27] found that the Medicines Transparency Alliance regulates the procurement of pharmaceuticals, drug policies, and drug supply, and establishes appropriate accountability in member states to promote transparency of drug information.…”
Section: Introductionmentioning
confidence: 99%
“…e world public medicine field is concerned with the reality of information transparency. e existing research focuses on the transparent supervision of drug information, transparency of the pharmaceutical industry chain in all aspects, and subject of participation [24][25][26]. For example, Vian et al [27] found that the Medicines Transparency Alliance regulates the procurement of pharmaceuticals, drug policies, and drug supply, and establishes appropriate accountability in member states to promote transparency of drug information.…”
Section: Introductionmentioning
confidence: 99%